2016
DOI: 10.4302/plp.2016.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength passively Q-switched Erbium-doped fiber laser with MWCNTs slurry as saturable absorber

Abstract: Abstract-In this work, a compact, stable dual-wavelength Qswitched laser has been demonstrated, with a multi-walled carbon nanotubes (MWCNTs) slurry as a saturable absorber (SA) which is independent of any host polymer. The MWCNTs slurry is fabricated and the peak shift is investigated using Raman spectroscopy.The passively Q-switched erbium-doped fiber laser (EDFL) oscillated simultaneously at 1532.32nm and 1556.97nm with 24.67nm peak separation, at threshold and maximum input power of 26mW and 74mW, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Feng et al [23] reported using a black-phosphorus polyimide film and generating the narrowest pulse width of all. On the other hand, multi-walled CNTs used by Zuikafly et al [24] gained the highest signal-to-noise ratio (SNR), which was valued at 62 dB. While Muhammad et al [25] obtained the highest tunability while using copper, Aziz et al [26], using zinc oxide, managed to generates the highest pulse energy and output power among the group.…”
Section: Laser Physicsmentioning
confidence: 99%
“…Feng et al [23] reported using a black-phosphorus polyimide film and generating the narrowest pulse width of all. On the other hand, multi-walled CNTs used by Zuikafly et al [24] gained the highest signal-to-noise ratio (SNR), which was valued at 62 dB. While Muhammad et al [25] obtained the highest tunability while using copper, Aziz et al [26], using zinc oxide, managed to generates the highest pulse energy and output power among the group.…”
Section: Laser Physicsmentioning
confidence: 99%
“…Therefore, the passive techniques based on saturable absorbers (SAs) are preferable due to their compactness and simplicity [5]. Up to date, various SAs including graphene and single walled carbon nanotube (CNT) were proposed and demonstrated for passively generating Q-switched pulses due to their excellent nonlinear optical characteristic [6][7]. However, these materials own some drawbacks such as, low optical saturation absorption per layer for graphene, while the CNT has its spectral range response depending on the chirality and size of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Q-switching is one of the main techniques to produce a train of energetic short pulses [1][2][3]. It can be passively achieved by deployment of saturable absorber (SA) device inside the laser cavity [4][5][6][7][8][9]. On the other hand, research on fiber lasers have been extensively carried out in recent years due to their many advantages such as simple structure, low cost, small size, and high environmental stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, SESAMs have many drawbacks, such as narrow working bandwidth and complex manufacturing packages and this has greatly limited their application in the development of pulsed fiber lasers. Therefore, many Qswitched fiber lasers have been demonstrated in recent years using various types of new SAs such as carbon nanotubes (CNTs) [5], graphene oxide [6], graphene [7], black phosphorus [8] and topological insulators (TIs) [9].…”
Section: Introductionmentioning
confidence: 99%